Organizational Factors Associated With Employees' Attitude Towards Training at Selected Financial Organization - Omar, Azman (2000)
In the researcher' s experience as the Training Manager for Abrar Group International (AGI) in 1995 - 1997. it was observed that AGI and its subsidiaries experienced a low turn-up trend for training programs. This posed many questions and assumptions. According to several authors such as Rubenson, Knowles and Cross, one of the reasons for this is employees' attitude towards training. However, there are many other possible factors affecting employee turn- up. The general objective of this study is to determine which organizational factors are associated with employees' attitude towards training at Abrar Group International. Specifically, this study is aimed to (l) identify the sociodemography of employees, (2) determine the attitude towards training among the employees, (3) determine the organization factors (the environment, job characteristics, supervisory support and the training barriers) with regard to their attitude on training, (4) determine the relationship of employee attitude towards training and selected independent variables (the organization factors), and finally (5) determine the predictor variable among the independent variables with regard to the respondents' attitude towards training. To start of the research, a preliminary questionnaire was prepared to validate and improve the survey instrument. This was fol lowed by a questionnaire survey research method using the validated and improved instrument. The instrument was administered on 160 employees from 16 subsidiaries of Abrar Group International (AGl) including the head office. A total of 144 valid responses were used for the study.